Analiza łańcucha tworzenia wartości zorientowana na jakość - Markowska, Małgorzata (Quality-oriented value chain analysis, 2006)
The value chain analysis focused on quality management system shows that quality must be considered as the value for customers. The basic issue in this integrated approach is quality of process which should be analyzed as regards quality, quality costs, efficiency measured financial and unfinancial indexes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 244-257